Lifetime-Based Tire Rotation Strategy to Minimize Premature Failure Cost Loss at Critical Position Dump Truck HD785-7 - M. Ferry Saputra; Laode Nuzul Fajrin; Kusnandar Kusnandar; M. Jailani Arrosyid; Fika Kurniawan (Journal of Social Research, 2025)
The coal mining industry faces significant challenges in managing operational costs, particularly those related to the maintenance of dump truck tires, which contribute 25–30% of total hauling operational expenses. This study examines a lifetime-based tire rotation strategy to minimize cost losses due to premature tire failures in positions 3 and 4 of HD785-7 dump trucks at the MIP mining site. The research method employs the Quality Control Circle (QCC) approach, consisting of eight systematic steps: problem identification, cause-and-effect analysis, solution determination, improvement implementation, result evaluation, and standardization. The implementation of the strategic tire rotation—by assigning tires with a lifetime of more than 8,000 hours to the 3rd and 4th positions, along with scheduled road patrols and optimized spare tire stock management—was carried out between April and August 2025. The results showed an 87% reduction in the loss cost for the left position (from IDR 291,947,858 to IDR 38,506,461) and a 65% reduction in the total loss cost for 27.00R49 tires (from IDR 404,792,592 to IDR 143,907,833), with the average lifetime progress of positions 3 and 4 increasing to 116% of the target. The scrap ratio changed from 5:3 (left:right) to 8:3, indicating the effectiveness of the rotation strategy in extending tire life at critical positions. This research makes a practical contribution to the mining industry by optimizing tire management through a predictive approach based on lifetime data and a comprehensive understanding of vehicle structural load distribution.